Representasi Matematis pada Pemecahan Word Problem Perbandingan Inkonsisten - Muttaqien, Anwar (JURNAL REVIEW PEMBELAJARAN MATEMATIKA, 2016)
Word problems solving involves the ability of translating and integrating word problem text. Many students get the difficulty in solving word problem due to their inability to translate and integrate word problem text into an exact representation. Representation is divided into two types namely, pictorial representation and schematic representation. This study aims at describing representation process employed by the 10th grade of High School students on word problem solving of inconsistent comparison. This research was done to 5 students and in this article have 3 subjects. The results of this study infine other representation. There are three mathematical representation of students in solving word problems comparison inconsistent: (1) pictorial representations, (2) schematic representation, and (3) pictorial-schematic representation.